Space‐Confined Seeded Growth of Cu Nanorods with Strong Surface Plasmon Resonance for Photothermal Actuation. Issue 27 (28th May 2019) - Chen, Jinxing; Feng, Ji; Yang, Fan; Aleisa, Rashed; Zhang, Qiao; Yin, Yadong
Abstract: Herein, we show that copper nanostructures, if made anisotropic, can exhibit strong surface plasmon resonance comparable to that of gold and silver counterparts in the near‐infrared spectrum. Further, we demonstrate that a robust confined seeded growth strategy allows the production of high‐quality samples with excellent control over their size, morphology, and plasmon resonance frequency. As an example, copper nanorods (CuNRs) are successfully grown in a limited space of preformed rod‐shaped polymer nanocapsules, thereby avoiding the complex nucleation kinetics involved in the conventional synthesis. The method is unique in that it enables the flexible control and fine‐tuning of the aspect ratio and the plasmonic resonance. We also show the high efficiency and stability of the as‐synthesized CuNRs in photothermal conversion and demonstrate their incorporation into nanocomposite polymer films that can be used as active components for constructing light‐responsive actuators and microrobots. Abstract : Hot rods : Copper nanorods (CuNRs) with tunable aspect ratios were grown in the confined space of preformed rod‐shaped polymer nanocapsules, thereby avoiding the challenges involved in the conventional synthesis. The obtained CuNRs have a strong plasmon resonance to incident light and efficiently convert the light into heat, making them suitable active components for constructing light‐responsive actuators and microrobots.